Using AI and Concerns in Corporate Learning - Kubovics, Michal (IJBLE Scientific Publications Community Inc., 2025)
The aim of this study is to explore the relationship between the frequency of using artificial intelligence (AI) technologies and the level of concerns about their implementation in Corporate Learning. Data were collected through an online questionnaire from 1308 respondents. The findings reveal a statistically significant, though weak, negative relationship indicating that respondents with higher frequency of AI use report lower concerns about its educational use. Contrary to expectations, older respondents demonstrated fewer concerns compared to younger ones. The regression analysis confirmed these results and indicated that additional factors might influence respondents' attitudes. Recommendations include publicly presenting the benefits of AI to alleviate concerns and encourage adoption by the mass population and business.